Wpływ małych i średnich przedsiębiorstw na konkurencyjność regionów - Zbadyński, Mariusz (The influence of small and medium enterprises on region's competitiveness, 2005)
As a result of the process of globalization and integration the competitiveness of regions has become an important category of theory and policy at the regional level. The development of a region depends, among others, on the development of economic activity on this terrain, in particular the development of small and medium-sized enterprises (SMEs). The author describes the impact of the regional environment on small and medium-sized enterprises development. The most important, in his opinion, is the activities of government and local authorities assisting local entrepreneurship. The article presents the regions as the performers of regional policy. It shows the mechanism of regional competitiveness improvement and the conditions of giving assistance to the subjects in that process.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1095, s. 34-44